Implementasi Program Magrib Mengaji Kota Bandung - Tri Asih Wismaningtyas (Publica: Jurnal Pemikiran Administrasi Negara, 2020)
The current modernization era and the development of electronic mass media has given birth to a shift in values, culture, and traditions of society, both in rural areas and especially in urban areas. The impact of this has given rise to very significant social changes in society, the impact of the good tradition of community groups at this time has been eroded by cultural acculturation and values that are at odds with the conditions and traditions of Indonesian society, including the culture of reciting after the evening prayer or regular prayers known as the evening recitation. The aim of this article is to focus on the implementation of Maghrib Mengaji. This research used a qualitative approach by literature study. The result of the research is Maghrib Mengaji is a part of the manifestation of Bandung Masagi, a religious education, national defense, culture and save the environment program. In the implementation, the Bandung City Government cannot conduct it alone. They need involve many community actors who could become a cooperative and interactive partnership. This research conclude that Maghrib Mengaji program was carried out well by professional and responsible networking actors. Further, this program recognized as a model for a pilot project for other regions in West Java Province.